Water Management through Indigenous Knowledge A Case of Historic Settlement of Bhaktapur City, Nepal - Gautam, Dipendra (Diplomica Verlag, 2014)
University,
Description based on publisher supplied metadata and other sources
Keywords: Indigenes Volk; Interkulturelle Kommunikation; Indigenous peoples -- Nepal; Intercultural communication -- Nepal; Water management -- Nepal